2021
DOI: 10.1017/pls.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Measuring attitudes as a complex system

Abstract: We test a method for applying a network-based approach to the study of political attitudes. We use cognitive-affective mapping, an approach that visually represents attitudes as networks of concepts that an individual associates with a given issue. Using a software tool called Valence, we asked a sample of Canadians (n = 111) to draw a cognitive-affective map (CAM) of their views on the carbon tax. We treat these networks as a series of undirected graphs and examine the extent to which support for the tax can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 97 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…This emphasizes the high face validity of the method. CAMs have already been applied as a tool to study political conflicts and general belief systems [97][98][99][100][101] and it has been shown that CAMs provide added value to empirical survey studies [102,103]. CAMs have also been applied to identify ethical values [cf.…”
Section: Motivation Of Methodologymentioning
confidence: 99%
“…This emphasizes the high face validity of the method. CAMs have already been applied as a tool to study political conflicts and general belief systems [97][98][99][100][101] and it has been shown that CAMs provide added value to empirical survey studies [102,103]. CAMs have also been applied to identify ethical values [cf.…”
Section: Motivation Of Methodologymentioning
confidence: 99%